Energy harvesting from living plant: a review on past research and way forward - Rahman, Sk Rakibur; Eng, Ngu Eng; Ashraf, Muhammad Aqeel; Pang, Wai Leong; Tan, Kar Ban; Singh, Ajay Kumar; Chan, Kah Yoong (Elsevier, 2025)
In the face of the global warming crisis, reliance on non-renewable energy sources poses significant ecological threats, prompting the international community to explore renewable alternatives. Numerous alternative energy sources are currently being studied, including solar, wind, hydropower, geothermal, plant-based, and biomass. This review highlights recent advancements in extracting energy from living plants by looking at 70 peer-reviewed research studies published from 2010 to 2025, including 15 that focused on Plant-Based Cells (PBCs), 24 on Plant Microbial Fuel Cells (PMFCs), and 21 that examined the physical traits of plants that influence how efficiently energy can be harvested. PMFC harnesses electron generation through the interaction of plant roots and soil bacteria during organic matter decomposition, while PBC captures electrical energy directly from the plant's metabolic processes via embedded electrodes. PMFCs typically generate lower voltage and power, whereas PBCs achieve significantly higher outputs, up to 3.5 V and 58.8 mW. The analysis examines key factors influencing energy efficiency, including plant species, age, soil composition, electrode materials, environmental conditions, and circuit design, and addresses scalability and integration challenges. The findings underscore the necessity for further research on optimal sizing, aging effects, and practical applications. Overall, this review aims to provide a solid foundation for advancing green energy technologies and their deployment in low-energy devices, such as IoT sensors, in smart farming and remote areas.